Politics and Community-Based Research Perspectives from Yeoville Studio, Johannesburg - Abed, Abdul (Wits University Press, 2019)
Politics and Community-Based Research: Perspectives from Yeoville Studio, Johannesburg offers a substantive and compelling analysis for a diverse readership interested in urban politics, community mapping and the built environment. The book draws on a critical reflection of Yeoville Studio, a research project conducted by Wits University academics from a diversity of disciplinary backgrounds, together with community partners and postgraduate students. A collection of vignettes portraying people and places in Yeoville interwoven with theoretically analytical chapters, it explores the politics of community research at a neighbourhood scale in its multiple facets, and will resonate with similar contested and complex neighbourhoods across the world. The mix of analysis, vignettes, photographs, architectural design and graphics builds the discussion in engaging, rich and integrated ways, to capture the many participatory approaches taken to this city-community studio.